Factors Affecting the Stock Price and Market Value of Equity -Survey Study on Companies Listed in Damascus Stock Exchange- - مالك حاتم اياد; محمد نذير (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to investigate the effect of some factors on market stock price and market value of Equity. The data is collected using annual financial reports for companies listed in Damascus Stock Exchange. These reports are available on Damascus Stock Exchange website. Using a dataset of 19 listed companies covering the period 2013 to 2020 comprising a total of 152 observations, Panel Data analysis is employed, with the help of the application Eviews 10 and Microsoft Excel 2010. The study found that there is a significant positive effect for the following factors: return on assets (ROA), return on equity (ROE), Turnover Ratio (TR), and Size on market stock price, whereas no effect is found between Book Value per share (BVPS) and market stock price. Moreover, the results showed there is a significant positive effect for the following factors: return on assets (ROA), return on equity (ROE), Turnover Ratio (TR), Book Value per share (BVPS), and Size on market value of Equity.